Tax obligation fulfillment - A. V. Krasyukov (Правоприменение)
The subject. The article is devoted to the study of the mechanism of tax obligation fulfillment. The author established that there are several points of view in understanding the legal essence of the fulfillment of an obligation in Russia and abroad: 1) contractual theories (the general contractual theory, the theory of a real contract, the limited contractual theory); 2) the theory of target impact; 3) the theory of real impact.The purpose of the article is to determine the legal essence of tax obligation fulfillment, to study the concept of the tax obligation fulfillment, the mechanism for exercising subjective rights and obligations, and the criteria for the proper fulfillment of a tax obligation.The methodology. The author uses general and specific scientific methods of scientific research: observation, systemic-structural, dialectical, analysis, comparative jurisprudence and others.The main results, scope of application. There are two sides of the tax obligation fulfillment: legal and factual. From an actual point of view, the tax obligation fulfillment is a set of operations by its parties with the object of the obligation. As a result, the object of the obligation must pass from one owner to another. From a legal point of view, the tax obligation fulfillment always represents the realization of its content through the exercise of rights and the fulfillment of obligations.The author believes that the tax obligation fulfillment should not be equated with the fulfillment of the obligation to pay tax, since not every obligation is executed through the payment of tax. In this regard, a situation may arise when the obligation is properly fulfilled by the debtor, and the creditor does not receive the property grant (for example, if a loss is received at the end of the tax period).The mechanism of the implementation of subjective tax rights and the fulfillment of obligations is a certain system of legal means and algorithms of behavior that allow to determine the appropriate size of the claim of a public law entity on the taxpayer's property and ensuring the transfer of the monetary is equivalent to this economic benefit to the budget system. This mechanism is a set of algorithms for the behavior of subjects of tax liability, defined by law, using specific legal means. As such means, depending on the party of the tax obligation, the law provides, for example, a tax return, a requirement to pay tax, etc. The mechanism of exercising subjective rights and fulfilling obligations includes the following stages: 1) pre-implementation; 2) procedural implementation; 3) actual implementation; 4) protection of the violated right.The author identifies five criteria for the proper fulfillment of a tax obligation: 1) the proper subjects of execution; 2) the proper place; 3) the proper time; 4) the proper object; 5) the proper way.Conclusions. The legal essence of the tax obligation fulfillment can be characterized as a transaction between its parties, aimed to mutual termination and the emergence of the rights of its parties. In order to protect the rights of bona fide taxpayers the author proposes to enshrine in tax legislation a ban on contradictory behavior in the process of fulfilling a tax obligation.